THE CHANGES IN ECONOMY AND IN AGRI-FOOD SECTOR IN POLAND - MACROECONOMIC ANALYSIS - Wigier, Marek (Economics of Agriculture, 2015)
Polish membership in the EU structures was a milestone which affected the acceleration of structural transformations in the entire national economy. In the period 2002-2014 the integration processes and the support of the agricultural policy was affected on structural changes in agribusiness sector. The purpose of this study is to assess the degree of development of agribusiness sector and the presentation the achievement related with Polands membership in the EU. Using the statistical and descriptive methods, has been carried an analysis of the Central Statistical Offce macroeconomic data with regard to assessing the degree of the structural changes in the economy and in the agro-food sector, the changes in food trade. Regarding to agriculture were represented among others changes in the agrarian structure, the income dynamics, regarding to food industry - amount of investments, the development of the output value etc.. The article conclusions are referred to macroeconomic and structural changes taking place in economy, in polish agriculture and in food industry.